Enhancement of DNA microarray images using mathematical morphological image processing - Bahari Jambek, Asral; Mat Said, Khairul Anuar; Sulaiman, Nasri (Universiti Putra Malaysia Press, 2017)
DNA microarray images contain spots that represent the gene expression of normal and cancer samples. As there are numerous spots on DNA microarray images, image processing can help in enhancing an image and assisting analysis. The mathematical morphology is proposed to enhance the microarray image and analyse noise removal on the image. This follows an experiment in which the erosion, dilation, opening, closing, white top-hat (WTH) and black top-hat (BTH) operations were applied on a DNA microarray image and its results analysed. Noise was completely removed by the erosion operation and the images were enhanced.